Land monitoring system: principles of formation and problems of development - Novakovska, I.; Matvieieva, I. (Land Management, Cadastre and Land Monitoring, 2023)
The article examines the structure, content and procedure of land monitoring, features of its development and legal regulation, substantiates the need to monitor the state of land in the process of decentralization of power and improvement of local self-government in Ukraine. Analyzing the relevance of land monitoring to the state environmental monitoring system as its constituent part, it was established that the specified norm is absent in the Regulation on land monitoring, which does not allow these monitoring to be considered a single system. The Regulations approved by the Ministry of Agrarian Policy on February 26, 2004 regarding soil monitoring have not yet been codified, and the agrochemical system of land certification as one of the sources of obtaining reliable information about soil cover has not been streamlined. It has been recognized as natural and timely to introduce monitoring of land relations and the development of pilot projects for their implementation and implementation in the country from September 1, 2017. The objects of this monitoring are presented, its tasks and essence are defined, and the peculiarities of the methodology of introducing land market monitoring into the monitoring of land relations are defined. It is emphasized that the selection of monitoring indicators corresponds to the practice of developed countries. At the same time, the principles of its implementation can be considered well-founded and objective. Ways to improve the Procedure for monitoring land relations, the draft of which has been published, and the monitoring of the land market are proposed.